Answer:
x=3
Step-by-step explanation:
When you substitute x = 3 to both equations, you get y = -4 for both so that is a solution
0.000000000224 i think thats the answer could be wrong
Using row 4:
<span>coefficients are: 1, 4, 6, 4, 1 </span>
<span>a^4 + a^3b + a^2b^2 + ab^3 + b^4 </span>
<span>Now adding the coefficients: </span>
<span>1a^4 + 4a^3b + 6a^2b^2 + 4ab^3 + 1b^4 </span>
<span>Substitute a and b: </span>
<span>a = 4x </span>
<span>
b = -3y </span>
<span>1(4x)^4 + 4(4x)^3(-3y) + 6(4x)^2(-3y)^2 + 4(4x)(-3y)^3 + 1(-3y)^4 </span>
<span>Now simplify the above: </span>
<span>256x^4 - 768x^3y + 864x^2y^2 - 432xy^3 + 81y^4 </span>
Answer:
because l1//l2 => z + 65 = 180
y + 65 = 90
x + 65 = 90
<=> z = 115
y = 25
x = 25